2017
DOI: 10.1111/jnc.13971
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol inhibits α‐synuclein aggregation in SHSY5Y neuroblastoma cells by a Calbindin‐D28k‐dependent mechanism

Abstract: Many neurodegenerative diseases are characterized by the formation of microscopically visible intracellular protein aggregates. a-Synuclein is the key aggregating protein in Parkinson's disease which is characterized by neuronal cytoplasmic Lewy body inclusions. Previous studies have shown relative sparing of neurons in Parkinson's disease and dementia with Lewy bodies that are positive for the vitamin D-dependent calcium-buffering protein, calbindin-D28k, and that a-synuclein aggregates are excluded from calb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In the 6-OHDA-induced PD model, pre- or post-treatment with 1,25(OH) 2 D 3 reduced tissue immunopositivity for TNF-α, partially restored tyrosine hydroxylase (TH) immunoreactivity, and prevented the decrease of VDR immunoreactivity in the lesioned striatum [ 133 , 134 ]. Cell culture studies revealed that the increased intracellular free calcium can induce the aggregation of α-synuclein, and proved that the increase of intracellular calcium and oxidative stress can act cooperatively to promote α-synuclein aggregation [ 135 138 ]. By reducing the expression of L -type Ca 2+ channels and increasing the expression of the plasma membrane Ca 2+ ATP-ase, NCX1, anti-apoptotic factor Bcl-2 and buffering protein calbindin D28k, 1,25(OH) 2 D 3 can maintain the low cytosolic Ca 2+ concentrations and thereby protect against Ca 2+ -induced oxidative damage in SN dopaminergic neurons [ 106 , 129 ].…”
Section: Main Textmentioning
confidence: 99%
“…In the 6-OHDA-induced PD model, pre- or post-treatment with 1,25(OH) 2 D 3 reduced tissue immunopositivity for TNF-α, partially restored tyrosine hydroxylase (TH) immunoreactivity, and prevented the decrease of VDR immunoreactivity in the lesioned striatum [ 133 , 134 ]. Cell culture studies revealed that the increased intracellular free calcium can induce the aggregation of α-synuclein, and proved that the increase of intracellular calcium and oxidative stress can act cooperatively to promote α-synuclein aggregation [ 135 138 ]. By reducing the expression of L -type Ca 2+ channels and increasing the expression of the plasma membrane Ca 2+ ATP-ase, NCX1, anti-apoptotic factor Bcl-2 and buffering protein calbindin D28k, 1,25(OH) 2 D 3 can maintain the low cytosolic Ca 2+ concentrations and thereby protect against Ca 2+ -induced oxidative damage in SN dopaminergic neurons [ 106 , 129 ].…”
Section: Main Textmentioning
confidence: 99%
“…Causal link [63] Transcription [62] Causal relationship [63] Regulatory T cells ↑ [112] Vit. D2 as suitable therapeutic candidate [128] Potential role of the VDR [138] Benefits after supplementation [139,140] Vit [92] Immunomodulatory effects [113] Ca 2+ homeostasis [114] Reduced oligomerization of prions [128] Inflammation [141] Ca 2+ homeostasis [142] Potential transcriptional regulation of HTT gene [150] Intervention studies Beneficial [58] Beneficial in dependence of genotype [87] Beneficial [115][116][117][118] Vit. D as genetic and environmental risk factor [ diseases and reduced Vitamin D level; however, it has to be emphasized that many aspects of vitamin D remain obscure in these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore vitamin D 3 administration was shown to prevent zinc-induced oxidative stress in substantia nigra of rat brain [91]. Oxidative stress and elevated intracellular-free calcium promote the aggregation of α-synuclein synergistically, and a recent study could show that the vitamin D 3 analogue calcipotriol is able to induce the expression of calbindin-D28k, thereby inhibiting the calcium-mediated aggregation of α-synuclein in human neuroblastoma cells [92].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Third, lewy bodies are abnormal aggregates of alpha synuclein that develops in neurons in PD. Vitamin D analogs can decrease intracellular-free Ca (II) and downregulate the expression of calbindin-D28k to reduce α-synuclein aggregation ( 48 ). However, so far its pathogenesis has not been completely figured out.…”
Section: Discussionmentioning
confidence: 99%